2019
DOI: 10.1111/jicd.12392
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tooth loss in adult Japanese dental patients: 8020 Promotion Foundation Study

Abstract: Although the number of missing teeth in Japanese adults is decreasing, persons aged ≥75 years tend to have at least 10 teeth missing, and approximately 30% have full dentures. 1 Tooth loss impacts mastication, speaking, swallowing, and esthetics. 2,3 Decreased masticatory ability due to tooth loss affects food intake, possibly leading to malnutrition. 4 Loss of multiple teeth is also associated with physical disability and cognitive decline, 5 and it can decrease the quality of life of elderly individuals.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
(33 reference statements)
3
17
0
Order By: Relevance
“…TL reportedly increases with age, and our results were similar. 42,43 The number of RT at BL was also significantly different between 28-24 and 23-20 RT and between 28-24 and ≤19 RT, but not between 23-20 and ≤19 RT (P = 0.99). These findings suggest that TL was less likely to occur if the number of RT at BL was ≥24 than ≤23.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…TL reportedly increases with age, and our results were similar. 42,43 The number of RT at BL was also significantly different between 28-24 and 23-20 RT and between 28-24 and ≤19 RT, but not between 23-20 and ≤19 RT (P = 0.99). These findings suggest that TL was less likely to occur if the number of RT at BL was ≥24 than ≤23.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have revealed significant loss of denture abutments. [42][43][44] Another explanation may be that patients with a low number of RT have received more restorative prosthetic treatment in the past and have more non-vital teeth. Some reports have also described significant loss of non-vital teeth.…”
Section: Discussionmentioning
confidence: 99%
“…There are too many factors affect a M2's life span [6,19], that's why to date there is no direct evidence revealing the relationship of M2 loss with their neighboring M3s. It's generally believed that the negative effect of M3s mainly occurred in the distal M2s [9,13,20], thus the prevalence of M2 loss due to diseases in the distal surface may reflect the influence of M3s on the adjacent M2s.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other teeth, many factors may affect a M2's life span, such as oral hygiene, occlusal condition, trauma, smoking, etc. [6]. Among the various risk factors to M2 pathology, the presence of its neighboring M3s has attracted increasing attention [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the risks of tooth loss [7][8][9]. Since individual-and tooth-level factors are involved in tooth loss, some studies have conducted multilevel analyses to identify the risk of tooth loss [10,11]. Tooth loss is associated with the type of dental visit and the risk of tooth loss was lower in those who had regular dental checkups compared with those who received treatment only [12,13].…”
Section: Introductionmentioning
confidence: 99%